Stability of a Dynamic Input-Output System: A Reply - Jorgenson, Dale W. (Review of Economic Studies, 1963)
Journal Article Stability of a Dynamic Input-Output System: A Reply Get access Dale W. Jorgenson Dale W. Jorgenson Berkeley Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 30, Issue 2, June 1963, Pages 148–149, https://doi.org/10.2307/2295813 Published: 01 June 1963